Young Men and the Creation of Civic Christianity in Urban Methodist Churches, 1880-1914 - Christie, Nancy (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2006)
AbstractThis article examines the formation and discourse of the Epworth League, established by the Methodist Church as a lay organization intended to keep adolescent boys in the church. While the Epworth League was ostensibly open to both men and women, its real aim was to masculinize a church which was perceived to be dominated by a female membership and female-led organizations. This article explores when and how this construction of youthful piety became embedded within Methodism and the impact it had on the shape of church governance. Moreover, it argues that social Christianity, which gained a foothold through the mechanism of the League was an essentially male-gendered discourse.